Politicking and emergent media US presidential elections of the 1890s - Musser, Charles 1951- (University of California Press, 2016)
"Presidential campaigns of the twenty-first century are not the first to use new media to promote their platform and marshal votes. In Politicking and Emergent Media, distinguished film historian Charles Musser looks at four US presidential campaigns during the long 1890s (1888-1900) as Republicans and Democrats mobilized a variety of media forms to achieve electoral victory. New York...the home of Wall Street, Tammany Hall, and prominent media industries...became the site of intense debate as candidates battled over voters' rights, labor issues, and currency standards for a fragile economy. If the city's leading daily newspapers were mostly Democratic as the decade began, Republicans eagerly exploited alternative media opportunities. Using the stereopticon (a modernized magic lantern), they developed the first campaign documentaries. Soon they were using motion pictures, the phonograph, and telephone in surprising and often successful ways. Brimming with rich historical details, Charles Musser tells the remarkable story of the political forces driving the emergence of new media at the turn of the century"...Provided by the publisher
Includes bibliographical references and index
Keywords: Geschichte 1800-1900; Geschichte 1890-1900; Geschichte; Massenmedien; Politik; Presidents -- United States -- Elections -- History -- 19th century; Mass media -- Political aspects -- United States; Press and politics -- United States -- History -- 19th century; Political campaigns -- United States -- History -- 19th century; Präsidentenwahl; USA; United States -- Politics and government -- 1885-1899